disguised reservations - موسى, وادي حسين; عبد, مصطفى سالم (Journal of Legal Sciences, 2021)
Concealed reservations are a trick that States resort to when they are prevented or acceded to treaties These countries make interpretative declarations but in fact Reservations are considered because they are intended to repeal or modify the legal effect of a particular text or provisions  of the treaty،  which is invalid and has no legal effect،  What makes disguised reservations invalid is that they are considered to be a infraction of general principles of international law and general principles of interpretation،  which is evident when analyzing and matching them.